Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.6026/97320630009426
|View full text |Cite
|
Sign up to set email alerts
|

Binding mode prediction of biologically active compounds from plant Salvia Miltiorrhiza as integrase inhibitor

Abstract: Integrase (IN), an essential enzyme for HIV-1 replication, has been targeted in antiretroviral drug therapy. The emergence of HIV-1 variants clinically resistant to antiretroviral agents has lead to the development of alternative IN inhibitors. In the present work, binding modes of a high potent IN inhibitor, M522 and M532, within the catalytic binding site of wild type (WT) IN were determined using molecular docking calculation. Both M522 and M532 displayed similar modes of binding within the IN putative bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The docking calculations showed that the major key interactions for stabilization of M 5 22 and M 5 32 binding are hydrogen bonding, metal-ligand, and π-π stacking interactions with adenosine base A17 of the viral DNA, while these key interactions were not observed with raltegravir [38]. Another molecular docking study was conducted for M 5 22 and M 5 32 inhibitors using of HIV-1 IN [39] instead of PFV IN [38]. The docking results with HIV-1 IN indicated that the binding modes of M 5 22 and M 5 32 were similar to those of 5-CITEP inhibitor [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The docking calculations showed that the major key interactions for stabilization of M 5 22 and M 5 32 binding are hydrogen bonding, metal-ligand, and π-π stacking interactions with adenosine base A17 of the viral DNA, while these key interactions were not observed with raltegravir [38]. Another molecular docking study was conducted for M 5 22 and M 5 32 inhibitors using of HIV-1 IN [39] instead of PFV IN [38]. The docking results with HIV-1 IN indicated that the binding modes of M 5 22 and M 5 32 were similar to those of 5-CITEP inhibitor [39].…”
Section: Discussionmentioning
confidence: 99%
“…To clarify potency of these two IN inhibitors, a recent reported study of molecular docking was conducted to determine the binding modes of M 5 22 and M 5 32 inhibitors within the catalytic core site of HIV-1 IN by using PFV IN model for WT (wild-type) and mutant variant, S217H mutant (equivalent to G140S/Q148H HIV-1 IN). The docking calculations showed that the major key interactions for stabilization of M 5 22 and M 5 32 binding are hydrogen bonding, metal-ligand, and π-π stacking interactions with adenosine base A17 of the viral DNA, while these key interactions were not observed with raltegravir [38]. Another molecular docking study was conducted for M 5 22 and M 5 32 inhibitors using of HIV-1 IN [39] instead of PFV IN [38].…”
Section: Discussionmentioning
confidence: 99%
“…S. officinalis is comprised of volatile oils, tannins, diterpenes, triterpenes, steroids, flavones and flavonoids [13,105,106]. They are well-known for various medicinal benefits (antioxidant, anti-inflammatory, anti-hyperglycemic, anti-dyslipidemia as well as culinary uses [107][108][109][110][111][112]. A study by Kianbakht et al [57] investigated the effects of S. officinalis leaf extract in combination with statin therapy in hypercholesterolemic T2DM patients, with positive findings that were deemed safe and further improved lipid profiles.…”
Section: Salvia Spp In Intervention Studiesmentioning
confidence: 99%
“…1) and lithospermic acid B (polycyclic phenolic carboxylic acids) were isolated from S. miltiorrhiza (Danshen, red sage) root extract and were shown to be potent and selective IIs [100]. Molecular docking calculations predicted that these compounds would be effective even in the case of HIV strains resistant to conventional therapy [101]. Using root of S. yunnanensis (another biological source of Danshen), researchers isolated polyphenol salvianolic acid N, which exhibited notable anti-HIV-1 activity and RT and integrase inhibition in vitro [102].…”
Section: Compounds With Anti-hiv Activitymentioning
confidence: 99%